Psychological motivation of Jim as a runaway slave in Mark Twain’s Adventures of Huckleberry Finn - Niken Khusnul Nibiya; Heri Dwi Santoso; Yesika Maya Ocktarani (EduLite: Journal of English Education, Literature and Culture, 2021)
‘Adventures of Huckleberry Finn’ is a great novel written in the nineteenth century by Mark Twain, the pen name of Samuel Langhorne Clemens. According to critics, this novel was written to criticise practices of slavery in the United States during his time, especially in states along the Mississippi river banks. This research aimed at explaining the hierarchy of needs of Jim and the motivations of his escape. The method used in this research was qualitative, with humans’ hierarchy of needs by Abraham Maslow employed. The analysis showed that the needs of Jim were divided into three phases, i.e., the phase of Jim as a slave, the phase of Jim as a runaway slave, and the phase of Jim as a free man. The results showed that there were four reasons why Jim decided to escape from Mrs. Watson, his master, i.e., 1) the master’s anger at Jim, 2) Jim’s conscience about himself as the object for capital gain, 3) his freedom as a human, and 4) his own happiness. It is concluded from the research that as a slave, Jim feels that his life needs cannot be fulfilled even when he is already free as long as he can never be reunited with his wife and children, who he thinks will give happiness to him. Based on the theory of Maslow’s hierarchy of needs, Jim’s higher level of need is love-and-belonging need.